Reproductive health of muslim women in Nepal: A case study of Mhammadpur VDC, bardiya district. - Teli, Aarif (2011)
ABSTRACT: This research is situated in a context where majority of Nepali women lack of access to quality reproductive health care. With only 10.2 percent of the rural women giving birth being attended by skilled birth attended, most women fall prey to causes of maternal deaths like hemorrhage, obstructed labor, abortion, entopic pregnancy or obstetric complications which are preventable. Muslim women are one of the marginalized groups of women in Nepal. Their marginalization has manifested into low reproductive health. This work entitled 'Reproductive Health Status of Muslim women in Nepal' not only attempts to analyze and clarify about reproductive health of Muslim women but also identify the influencing factors of reproductive health such as their social status and religious values. This research also aims to identify the needs of women to access RH rights, list of priority areas and identify issues and practices that cause adverse RH of Muslim women. The research has adopted exploratory, descriptive and explanatory type of research design. The research shows that Muslim women in Mohammadpur VDC have not been able to progress from highly conservative traditional practices. The education quality of the women in dire condition as many is unable to write their names. The women are unaware about their RH rights and are very reluctant to take health services provided in the area. The lack of awareness and low economic status among the Muslim has resulted in early marriage and early motherhood, no antenatal care and reproductive health.